Synthesis and Modification of Clinoptilolite - Ambrozova, Pavlina (Molecules, 2017)
Clinoptilolite is a natural mineral with exceptional physical characteristics resulting from its special crystal structure, mainstreamed into a large zeolite group called heulandites. An overall view of the research related to the synthesis, modification and application of synthetic clinoptilolite is presented. A single phase of clinoptilolite can be hydrothermally synthesized for 1–10 days in an autoclave from various silica, alumina, and alkali sources with initial Si/Al ratio from 3.0 to 5.0 at a temperature range from 120 to 195 °C. Crystallization rate and crystallinity of clinoptilolite can be improved by seeding. The modification of clinoptilolite has received noticeable attention from the research community, since modified forms have specific properties and therefore their area of application has been broadening. This paper provides a review of the use of organic compounds such as quarter alkyl ammonium, polymer, amine and inorganic species used in the modification process, discusses the processes and mechanisms of clinoptilolite modification, and identifies research gaps and new perspectives.